H3PW12O40 (HPA), an Efficient and Reusable Catalyst for Biodiesel Production Related Reactions. Esterification of Oleic Acid and Etherification of Glycerol - Sepulveda Flores, Jorge Humberto (2011)
In esterification of oleic acid with methanol at 25 °C HPA displayed the highest activity. Moreover the HPA could be reused after being transformed into its cesium salt. In the reaction of etherification of glycerol HPA and Amberlyst 35W showed similar initial activity levels. The results of acid properties demonstrate that HPA is a strong protonic acid and that both surface and bulk protons contribute to the acidity. Because of its strong affinity for polar compounds, HPA is also seemingly dissolved in both oleic acid and methanol. The reaction in this case proceeds with the catalyst in the homogenous phase.